European Data Protection: In Good Health?
XVIII, 363 p. 20 illus., 10 illus. in color.
Keywords: Although Europe has a significant legal data protection framework, built up around EU Directive 95/46/EC and the Charter of Fundamental Rights, the question of whether data protection and its legal framework are ‘in good health’ is increasingly being posed. Advanced technologies raise fundamental issues regarding key concepts of data protection. Falling storage prices, increasing chips performance, the fact that technology is becoming increasingly embedded and ubiquitous, the convergence of technologies and other technological developments are broadening the scope and possibilities of applications rapidly. Society however, is also changing, affecting the privacy and data protection landscape. The ‘demand’ for free services, security, convenience, governance, etc, changes the mindsets of all the stakeholders involved. Privacy is being proclaimed dead or at least worthy of dying by the captains of industry; governments and policy makers are having to manoeuvre between competing and incompatible aims; and citizens and customers are considered to be indifferent. In the year in which the plans for the revision of the Data Protection Directive will be revealed, the current volume brings together a number of chapters highlighting issues, describing and discussing practices, and offering conceptual analysis of core concepts within the domain of privacy and data protection. The book’s first part focuses on surveillance, profiling and prediction; the second on regulation, enforcement, and security; and the third on some of the fundamental concepts in the area of privacy and data protection. Reading the various chapters it appears that the ‘patient’ needs to be cured of quite some weak spots, illnesses and malformations. European data protection is at a turning point and the new challenges are not only accentuating the existing flaws and the anticipated difficulties, but also, more positively, the merits and the need for strong and accurate data protection practices and rules in Europe, and elsewhere.